Takotsubo syndrome after mitral valve surgery: a case report. Issue 6 (22nd November 2020) - Devesa, Ana; Hernández-Estefanía, Rafael; Tuñón, José; Aceña, Álvaro
Abstract: Background: Takotsubo syndrome is a frequent entity; however, it has never been described after a mitral valve surgery. Case summary : We present the case of a 79-year-old woman, with background of atrial fibrillation and a left atrial appendage closure device, who was admitted for elective mitral valve replacement, because of asymptomatic severe primary mitral regurgitation. Biologic mitral valve was implanted without incidences, but in the postoperative, she developed cardiogenic shock. Electrocardiogram (ECG) showed inverted T waves in precordial leads and an echocardiography showed severe left ventricular (LV) dysfunction with mid to distal diffuse hypokinesis, and better contractility in basal segments. Troponin levels were mildly elevated. With the suspicion of a postoperative acute coronary syndrome, a coronary angiography was performed and showed no significant coronary lesions. The haemodynamic situation was compromised for the next 48 h, in which vasoactive support and intra-aortic balloon counterpulsation were implemented. After 48 h, the haemodynamic situation suddenly improved. The ECG was normalized, and a control echocardiogram showed partial recovery of the LV function with resolution of regional wall motion abnormalities. The patient could be discharged at 1 week. The clinical picture was interpreted as a stress cardiomyopathy after mitral valve surgery. Discussion : Takotsubo syndrome is a threatening condition; complications in acute phase could lead to a fatal outcome. Mitral valve surgery has to be considered as a trigger for this entity, after excluding coronary involvement, specially of left circumflex artery.